Deciphering changes in photophysical properties of carbon dots and protein conformations induced by bioactive molecules - Kaur, Mandeep (My University, 2025)
The thesis entitled “Deciphering changes in photophysical properties of carbon dots and protein conformations induced by bioactive molecules” is divided into five chapters. Chapter-1 It describes the background information on proteins, biomolecules, bile salts, nanomaterials, nanosensor and deep eutectic solvents together with literature survey and scope of the work. This chapter provides detailed information on the significance of protein interactions with bioactive molecules (bile salts), carbon dots (CDs), its synthesis approaches, fluorescence mechanisms along with their optical properties and applications, newly emerged green deep eutectic solvents were also discussed. Are also discusses the various fluorescence quenching mechanisms of CDs in the presence of quenchers and their photophysical factors like UV-Visible absorption, steady state and time-resolved fluorescence studies, photostability, photoluminescence quantum yield, etc. Chapter 2 of the thesis includes a brief summary of the characterization techniques used in all of the experiments undertaken throughout the thesis. The widely used characterization techniques used includes UV-Visible spectroscopy, steady-state fluorescence spectroscopy, time-resolved fluorescence spectroscopy, high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), energy dispersive spectroscopy (EDS), attenuated total reflectance Fourier-transform infrared (ATR FT-IR) spectroscopy, Raman spectroscopy, grazingincidence X-ray diffraction (GIXRD), and zeta potential measurements are among the most widely utilized methods for characterization. These are utilized to better understand the interactions between protein and bile salts, as well as to research the physical, chemical, and optical properties of biomass-derived carbon nanoparticles, along with their practical usefulness as a nanosensor as well as the underlying mechanism. Bile salts are physiologically-important natural amphiphilic biosurfactants synthesized in the liver and play a vital role in the solubilization and digestion of dietary lipids, cholesterol, and other fatsoluble compounds in the body. Bile salts also exhibit pharmacological and biological uses asxx carriers for transporting poorly water-soluble drugs and other chemicals owing to their unique emulsifying, solubilizing capacities and micelle forming ability. In this context, we present an endeavour towards elucidating the interaction and binding between the most abundant plasma protein namely, human serum albumin (HSA) and bile salts to demonstrate an intriguing interplay of hydrophobic, electrostatic and hydrogen bonding effects using steady state absorption, fluorescence emission, anisotropy, time-resolved emission, and molecular modelling approaches. The outcome illuminates how amphiphilic interfaces of bile salts under various physico-chemical conditions trigger the conformational changes and binding affinities of native and molten-globule forms of HSA. To elucidate non-covalent interactions during HSA-bile salt supramolecular hostguest complex formation, changes in intrinsic (tryptophan) and extrinsic (ANS) fluorescence have been investigated. The results reveal upon binding of bile salts in subdomain IIA of HSA, the protein undergoes conformational changes mediated primarily by hydrophobic interactions. Furthermore, time-resolved fluorescence measurements provide important structural and dynamical insights into the protein-bile salt supramolecular complexes. Additionally, molecular docking studies on these complexes clearly reveal spontaneous binding of bile salts into subdomain IIA of HSA while suggesting that the binding affinity decreases with the decreasing order of hydrophobicity of the bile salts (NaDC>NaC>NaTC) (ΔGdock = -29.64 kJ mol-1, -26.15 kJ mol-1, -14.35 kJ mol-1) respectively. This study exclusively highlights the molecular mechanism of conformational perturbation in native (pH 7) and molten-globule (pH 3) forms of HSA, induced by bile salts. We believe that the results reported herein will be helpful in the design and formulation of protein-bile salt-based pharmacological carriers suitable for drug delivery. Riboflavin (RF) detection is essential for controlling nutritional health due to its increasing significance in the food and pharmaceutical industries. Regular daily intake of RF (vitamin B2) is important because it is not synthesized and stored in the human body in appreciable amounts. Therefore, an efficient and biocompatible nanosensor with good selectivity and sensitivity for RF detection is required. CDs derived from biomass have recently attracted interest in environmental science due to their simple, cost-effective methods of synthesis, as well as their sustainability advantages and practical implications. Herein, we demonstrate the utility of a ratiometric fluorescence-based CDs nanosensor for the detection of RF in its isolated, pure form as well as inxxi pharmaceutical tablets. We report the synthesis, characterization, and sensing potential of intrinsic nitrogen-functionalized carbon quantum dots (N-CDs) from Indian gooseberry (a renewable biomass precursor) using a microwave assisted pyrolysis method that involves a green methodology. High-resolution transmission electron microscopy (HRTEM) indicated that N-CDs are monodisperse with an average diameter of ∼8.1 nm. Fourier-transform infrared (FTIR) and Xray photoelectron spectroscopy (XPS) validated intrinsic nitrogen functionalization and the presence of amino, hydroxyl, and carboxyl groups on the surface of N-CDs. Further, X-ray diffraction (XRD), UV-Visible and fluorescence spectroscopy, and time-correlated single photon counting (TCSPC) measurements were also employed for the characterization of N-CDs. The asprepared nanoprobe exhibits bright green emission with a remarkable fluorescence quantum yield of ∼48%. Moreover, N-CDs are highly water-soluble and are extremely stable in a range of pH, ionic strength, and photoirradiation. Additionally, N-CDs selectively and specifically detect RF (vitamin B2) in aqueous media w.r.t various bio-analytes with a limit of detection (LOD) ∼35 nM. Our nanosensor can also detect vitamin B2 present in commercially available pharmaceutical tablets with an LOD of ∼61 nM. Mechanistic studies confirmed that sensing involves fluorescence resonance energy transfer (FRET) between RF and N-CDS interfaces. Overall, the present work provides a new vision for the development of an innovative and sensitive approach of a green fluorescent nanosensor for the detection of RF which may find potential applications in the pharmaceutical and food industries. The significant toxicity and environmental persistence of 4-nitrophenol (4-NP) create an urgent need for eco-friendly, effective detection methods. Due to its persistence, toxicity, and carcinogenicity, 4-NP has been classified by the U.S. Environmental Protection Agency as a primary pollutant. It commonly contaminates the environment, primarily as a byproduct of the pharmaceutical industry. In biological systems, 4-NP can cause significant damage to organs such as the liver and kidneys, impair central nervous system function, and contaminate the bloodstream. To address the challenge of 4-NP detection, the study introduces a novel and sustainable detection technique using nitrogen and chlorine co-functionalized carbon dots (abbreviated as S-CDs). The synthesis protocol was employed through hydrothermal method, using sucrose as a carbonxxii precursor and deep eutectic solvent (DES) composed of choline chloride and urea in a 1:2 molar ratio. The synthesized nanosensor exhibited brilliant green fluorescence under UV light, showed excellent water solubility, high photostability with a quantum yield value of ∼56%. HRTEM analysis revealed that the S-CDs were spherical, monodisperse, and had an average diameter of 3.06 nm. FTIR and XPS analyses confirmed intrinsic nitrogen and chlorine functionalization, showing the presence of amino, hydroxyl, carboxyl, and chlorine groups on the surface of S-CDs. Further characterization of S-CDs included X-ray diffraction (XRD), ultraviolet-visible (UV-Vis) spectroscopy, fluorescence spectroscopy, and time-correlated single photon counting (TCSPC) studies. The nanoprobe exhibited high selectivity and sensitivity for 4-nitrophenol (4-NP), with a detection limit of 10 nM. Mechanistic studies verified an inner filter effect (IFE) mechanism between S-CDs and 4-NP, with significant spectral overlap and no change in average lifetime values, attributed to the formation of a zwitterionic spirocyclic Meisenheimer complex. Additionally, photophysical parameters, including quenching efficiency and binding constant, were also assessed to further understand the sensing mechanism. This work paves the way for developing a sensitive, green fluorescent nanosensor for rapid, cost-effective and environmentally friendly approach as well as on-site detection of 4-NP, offering a promising tool for pollution monitoring and control for environmental water samples
Keywords: Human serum albumin; Bile salt; Protein surfactant interaction; Fluorescence; Molecular modeling